Partial nephrectomy can be a successful treatment option for renal epithelioid angiomyolipoma: a case report and literature review - Liulytė, Aurelija; Žalimas, Algirdas; Meškauskas, Raimundas; Ušinskienė, Jurgita; Jankevičius, Feliksas (Acta medica Lituanica, 2020)
Background. Renal epithelioid angiomyolipoma is a rare tumour which involves kidneys in most cases. It is known for its aggressive behaviour as a significant number of cases have been associated with metastatic epithelioid angiomyolipoma. Usually, radical treatment with systemic therapy is recommended. Only a small number of cases of epithelioid angiomyolipomas have been reported with the standard treatment being radical or partial nephrectomy. We present a case report showing that partial nephrectomy can be a successful treatment option for renal epithelioid angiomyolipoma. This is the first case of this nature in Lithuania. Case presentation. In this case, a 40-year-old male with epithelioid angiomyolipoma of the left kidney is presented. In 2012, a cystic left renal mass 40 × 41 mm in size was diagnosed incidentally while performing ultrasound and later confirmed by MRI. Due to the size of the tumour and the possibility of renal cell carcinoma, surgery was scheduled. Left partial nephrectomy was performed successfully. Final pathology report came back with the diagnosis of renal epithelioid angiomyolipoma. The patient had yearly follow-up for six years by CT scan, and neither recurrence nor progression were observed. Conclusion. Early detection and diagnosis are crucial for treatment as the tumour tends to have malignancy potential. With early diagnosis, partial nephrectomy can be performed with yearly follow-up and no systemic treatment required.
Keywords: epithelioid angiomyolipoma; magnetic resonance imaging; partial nephrectomy; systemic treatment